Principles of web design - Sklar, Joel (Thomson, Course Technology, 2006)
This latest edition of Joel Sklar's Principles of Web Design will help students build on their HTML skills to enhance Web pages and gain a critical eye for evaluating Web site design. Updated for the latest Web design technologies, this text has increased coverage of XHTML and Cascading Style Sheets to keep your curriculum up to date. Screen shots and browser information have been updated to reflect the latest, most current Web trends and technology. This text will provide the solid foundation students need to build successful Web sites